Bamboo Crafts Business Development Model Reviewed From The Perspective Of Maslahah - Adelia Fitra Gustari; Muhammad Arif; Muhammad Lathief Ilhamy Nasution (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Bamboo is a versatile plant with superior ecological properties, offering great potential for the development of craft businesses that are sustainable and beneficial to society. This research aims to formulate a bamboo craft business development model based on the concept of maslahah, namely realizing benefits and benefits for all parties involved. Bamboo craft art is a local product produced by skilled hands so that it produces unique products and has economic value. Bamboo craft products are no longer foreign to us, especially to people from Sidodadi Village, Beringin. The business model of innovation in the bamboo craft business aims to develop products to create products that are efficient and competitive. The method used in this research is a qualitative method with an observation and interview approach. The aim of this research is to find out and examine how the bamboo craft business development model is viewed from a maslahah perspective. The results of this research show that this research does not provide benefits because there is still a lack of employee welfare, there is no development of product models, and distribution is not wide enough and the quality of raw materials is not good